Diophantine Frequency Synthesizer Design for Timekeeping Systems. (11th December 2007) - Sotiriadis, Paul P.; Weaver, Gregory L.
Abstract : Diophantine Frequency Synthesis (DFS), a number-theoretic approach to the design of very high resolution frequency synthesizers, was introduced in 2006. Further work concerning the impact of controlling mixing products for high-spectral purity was addressed and reported at the 2007 European Frequency and Time Forum. The focus of this paper is on the implementation of nested DFS architectures targeting microphase-type applications for precision timekeeping systems. We have shown that DFS does not impart any extraordinary design constraints on spectral purity in comparison to commonly used high resolution frequency synthesis techniques such as DDS or fractionalN . Here we describe a design approach for 10 MHz synthesizers with 1E-13 fractional resolution in consecutive steps ranging± 10  Hz. The synthesizers generate their output from a 10 MHz reference standard. Such synthesizers are essential to accomplishing precision frequency correction in timekeeping systems.